Salivary cortisol and cortisone responses to tetracosactrin (synacthen). (September 2015) - Cornes, Michael P; Ashby, Helen L; Khalid, Yasmeen; Buch, Harit N; Ford, Clare; Gama, Rousseau
Background: To establish cutoff values for salivary liquid chromatography tandem mass spectroscopy cortisol and cortisone in defining adequate adrenocortical function during a standard synacthen test. Methods: We compared salivary liquid chromatography tandem mass spectroscopy cortisol and cortisone responses to those of serum cortisol measured on the Roche E170 immunoassay analyser and the Abbott Architect i2000 before and 30 min and 60 min following 0.25 mg of intravenous synacthen. Results: Correlations of salivary cortisol and cortisone were bimodal and linear, respectively. Based on these correlations, adequate salivary cortisol and cortisone responses to synacthen were extrapolated from a serum cortisol (Roche) cut-off of 550 nmol/L and defined as 15 nmol/L and 45 nmol/L, respectively. The Abbott method correlated well with the Roche but gave results that were about 20% lower than the Roche method. Conclusions: Measurement of salivary cortisol and cortisone responses offers an alternative to those of serum cortisol during a synacthen test in the investigation of adrenal hypofunction.